Segregação socioambiental: estudo de caso no bairro colôniaventura/Tefé-AM a partir de uma perspectiva geográfica - Antonio Jucivan Martins Bruce; Eubia Andréa Rodrigues (Confins)
The process of urbanization has triggered contention and dispute that are observed in the perceptibility of what is shaped by the city, which according to Spósito "is the place of concentration and vivacity of social, economic, political and cultural life" (2008, p.13). It is within this circumstance that Tefé emerges as a town that has standardized itself and was built with these attributions, as a fragmented, articulated and unequal space (CORRÊA, 1995) which has promoted a dispute of socio-environmental segregation, this being identified in the Neighborhood of Cologne Ventura, in view of its residents suffer from discriminatory labels (gang member, potheads, drug addicts, thieves, etc.) from outside residents. From this perspective, the research was established, with attention on how man settles in the territory to produce and reproduce. His space emerged with the need to identify the elements that guide the occupation of the neighborhood to understand the desires of the residents, considering the time of creation of the same, since it is most recent in the town of Tefé (2000). The methodological methods were based on an empirical analysis with a quantifiable characteristic, derived from a dialogue between those involved. For this reason, the research was carried out in order to show and collaborate with public authorities together with appropriate agencies the problems identified. In this conclusions, the results intent to reflect and instigate the theme in question, with the purpose of promoting public policies with social and environmental justice for the residents of the Cologne Ventura neighborhood.